Combined application of biochar with compost and fertilizer improves soil properties and grain yield of maize. (2nd January 2018) - Naeem, Muhammad Asif; Khalid, Muhammad; Aon, Muhammad; Abbas, Ghulam; Amjad, Muhammad; Murtaza, Behzad; Khan, Waqas-ud-Din; Ahmad, Naveed
ABSTRACT: A pot study was conducted to assess the combined effect of biochar (B) with compost (Com) and inorganic fertilizers (F) for improving nutrient acquisition and productivity of maize. Seven different treatments, including B (1% w/w), F (Recommended nitrogen, phosphorus and potassium (NPK): 60, 30 and 25 mg kg ─1 ), Com (1.5% w/w), Com+F (1.5% + NPK), B+F (1% + NPK), B+Com (0.5% + 0.75%), B+Com+F (0.5% + 0.75% + NPK) along with a control (C) without B, Com and F were applied in pots with four replications. The results showed that growth and grain yield of maize increased by the application of B, Com and F compared with C, but B+Com+F was more effective than their sole application (i.e. B, Com and F). Highest leaf chlorophyll content, gas exchange attributes and nutrient concentrations: N, P and K in shoot and grains were observed, where B+Com+F was applied followed by Com+F > B+F > B+Com > F > Com > B > C. Soil properties such as soil organic carbon (SOC), N, P, and K were significantly increased, whereas soil pH was decreased by the combination of B with Com and F. Hence, application of B in combination with Com and F (B+Com+F) could be a good management strategy to enhance crop productivity and improve soil properties.